1999
DOI: 10.1046/j.1365-2648.1999.01134.x
|View full text |Cite
|
Sign up to set email alerts
|

Reflective inquiry framework for nurse administrators

Abstract: Problematic situations comprise a significant proportion of nurse administrators' practice. Reflective inquiry is recommended as a method for identifying the problem and its solution. This approach is consistent with pragmatic philosophy which recognizes the fallacy of basing one's action on an a priori conclusion. Dewey's elements of reflective inquiry are used as the framework to analyse its relevance to administrative practice. Emphasis is placed on the importance of using empirical observations and thought… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…However, skills, gained through experience, can be passed on to new learners to enhance and speed their learning (Antrobus 1997), or assist job‐shadowing and critical questioning (Carkhuff 1996). Reflexive practice is likely to be useful both in administrative roles in health care settings and in clinical roles (Schmieding 1999).…”
Section: Research Evidence: a Facilitative Context For Collective Leamentioning
confidence: 99%
“…However, skills, gained through experience, can be passed on to new learners to enhance and speed their learning (Antrobus 1997), or assist job‐shadowing and critical questioning (Carkhuff 1996). Reflexive practice is likely to be useful both in administrative roles in health care settings and in clinical roles (Schmieding 1999).…”
Section: Research Evidence: a Facilitative Context For Collective Leamentioning
confidence: 99%
“…Based on recent research on reflection (e.g. Haddock & Bassett 1997, Kim 1999, Schmieding 1999), it can be assumed that this is one important reason behind the differing conceptions and why, for example, some nurse managers placed more emphasis on the contribution of peer supervision than did the others. All the interviewees were, however, satisfied with the contribution of peer supervision, so it can be assumed that they knew how to use peer supervision in the best possible way in quality management in their work.…”
Section: Interpretation Of the Findingsmentioning
confidence: 99%
“…Problem situations are an important part of the practice of administrative nurse managers and clinical nurses. (31) Being more skilled on problem solving is attributed to nurse managers. However, as clinical nurses and nurse managers may replace each other according to functioning of the clinic, problem solving skills are among the skills clinical nurses should also…”
Section: Discussionmentioning
confidence: 99%
“…Nurses must possess a positive self-image and professional identity in order to provide optimal professional care for patients. (31) When ATQ scores of the nurses were evaluated, it was found that the nurses who said they were not satisfied with their professions had higher ATQ scores. In the literature, it is reported that automatic thoughts in nurses are based on the stress related to their professions.…”
Section: • Researchmentioning
confidence: 99%